Fetus in fetu with jaundice- A rare presentation of a rare disease - Khan, Sifat Zereen; Huq, Md Ashraf Ul; Hossain, Tahmina; Huque, Mohammed Moinul; Adil, Syed Md; Das, Sahadeb Kumar; Sharif, H M Zafar; Alam, S M Shafiqul (Journal of Paediatric Surgeons of Bangladesh, 2018)
Fetus and fetu is a rare mysterious medical phenomenon in which an acardiac fetiform mass is commonly located in abdomen of a neonate or infant. We report on a case of a 7 month-old girl with a gradually enlarging right upper abdominal mass and progressive jaundice, whose plain abdominal radiograph, ultrasonography, and computed tomography scan revealed a mass in which the contents favor a fetus in fetu. Obstructive jaundice was caused by billiary obstruction by FIF . Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (2): 61-65